Fossil record improves biodiversity risk assessment under future climate change scenarios. Issue 8 (31st May 2017) - Lima‐Ribeiro, Matheus S.; Moreno, Ana Karolina M.; Terribile, Levi C.; Caten, Cléber T.; Loyola, Rafael; Rangel, Thiago F.; Diniz‐Filho, José Alexandre F.
Abstract: Aim: Conservationists have been using ecological niche modelling (ENM) to understand how climate change impacts species, estimate their extinction risk and assess species conservation status in the future. However, most ENMs are built using just current species occurrences. As short‐term observations are naturally biased and incomplete in both geographical and climate spaces, palaeontologists have recommended the use of fossil data to improve species vulnerability assessments. Here, we used a time structured data set of the jaguar Panthera onca (Linnaeus, 1758) to test the implications of fossil data on distinct distribution dynamics and conservation status predicted by ENMs under future climate change scenarios. Location: The New World. Methods: We built two classes of ENMs, (i) using only current occurrences of P. onca and (ii) combining current and fossil information. Models were then projected onto current and future climates. Results: Niche models calibrated using fossil data broadly predicted more optimistic conservation statuses, with larger suitable areas for the species in the future, which are geographically nearest to its current distribution and better represented within protected areas (current network of protected areas will hold significant suitable areas). Main conclusions: Fossils provided complementary information about different climate conditions that species experienced though time and filled empty spaces in currently unoccupied fundamental niche. Our analyses reinforce the idea the fossil record is a valuable source of alternative information to increase the reliability of ENMs when assessing biodiversity risk. Combining ecological and palaeontological data for niche modelling increase our understanding about species responses to changing climates. Consequently, it potentially improves our knowledge on how to manage biodiversity by more reliably anticipating the effects of climate change and proactively—rather than reactively—planning conservation actions over longer periods going forward.